Where do new Ph.D. economists go? Evidence from recent initial job placements - Jihui Chen; Qihong Liu; Sherrilyn M. Billger (Institute for the Study of Labor (IZA), 2012)
We use data from the 2007-2008 Ph.D. economist job market to investigate initial job placement in terms of job location, job type, and job rank. Our results suggest gender differences in all three dimensions of job placement. Relative to their male counterparts, female candidates are less (more) likely to be placed into academic (government or private sector) jobs and, on average, are placed into worse ranked jobs. Foreign female candidates are also more likely than foreign males to stay in the U.S. When foreign students are placed outside the U.S., they are more likely to be in academia than in government or private sector, while the opposite holds when foreign students are placed in the U.S., which is largely consistent with a stylized theory model. Our results also reveal various country/region heterogeneities in the type, location, and rank of job placements.
Keywords: A11; A23; J44; 330; Ph.D. labor market; job type; job location; job rank; Ökonomen; Arbeitsmarkt; Geschlecht; Beruf; USA